Analisis Peran Kepolisian Daerah (Polda) Sulut dalam Pengembangan Health Tourism di Wilayah Hukum Sulawesi Utara - Faridah Alkatiri; Gustaaf A. E. Ratag; Aaltje E. Manampiring (Universitas Sam Ratulangi, 2023)
Tourist safety and security play an important role in the image of a destination to increase tourist visits. North Sulawesi Province as one of the regions that is currently intensively promoting its regional tourist destinations and cooperation between the local government, tourism office, health facilities, and the Police. This study aimed to analyze the contribution of the North Sulawesi Regional Police to the management of tourist events according to the factors that hindered the North Sulawesi Regional Police, and the efforts and strategies that had been carried out by the North Sulawesi Regional Police in developing health tourism. This was a descriptive and qualitative study. Primary data were obtained through in-depth interviews and using interview guidelines. Data analysis was carried out using the interactive Miles and Hubberman model. The results showed that the role of the police in developing health tourism was carried out quite well, albeit it was not optimal. Obstacles to the police in carrying out their role, namely the absence of a tiered system regarding inter-regional security arrangements and a system for reporting the security of tourists and the absence of coordination between relevant stakeholders, and the regional police in carrying out the main duties of Keskamtibmas. The health tourism program must be known by all parties, a digital system that clearly regulated the security duties of the regional police, and coordination of all relevant stakeholders. In conclusion, North Sulawesi has the potential to advance the tourism industry, especially health tourism, but the contribution of the regional police in the development of health tourism is still not optimal. Keywords: health tourism; tourist safety; Regional Police Abstrak: Keselamatan dan keamanan wisatawan berperan penting dalam membangun citra destinasi untuk meningkatkan kunjungan wisatawan. Provinsi Sulawesi Utara tengah gencar memromosikan destinasi wisata daerahnya dan membangun kerjasama antara pemerintah daerah, Dinas Pariwisata, fasilitas kesehatan, dan Kepolisian Daerah (Polda). Penelitian ini bertujuan untuk menganalisis kontribusi Polda Sulawesi Utara (Sulut) dengan pengelola tempat wisata sesuai faktor-faktor yang menghambat Polda Sulut, dan upaya serta strategi yang telah dilakukan Polda Sulut dalam pengembangan health tourism. Jenis penelitian ialah kualitatif deksriptif. Pengambilan data primer melalui in-depth interview dan pedoman wawancara. Analisis data menggunakan model interaktif Miles dan Hubberman. Hasil penelitian menunjukkan bahwa peran Kepolisian dalam pengembangan health tourism telah dilaksanakan cukup baik namun masih kurang maksimal. Hambatan Kepolisian dalam menjalankan perannya yaitu belum adanya sistem berjenjang mengenai pengaturan pengamanan antar wilayah dan sistem pelaporan pengamanan wisatawan, serta belum adanya koordinasi stakeholder terkait dengan polda dalam menjalankan tugas pokok Keskamtibmas. Program health tourism harus diketahui oleh semua pihak, adanya sistem secara digital yang mengatur secara jelas tugas pengamanan Polda serta adanya koordinasi setiap stakeholder terkait. Simpulan penelitian ini ialah Sulawesi Utara telah memiliki potensi untuk memajukan industri pariwisata khususnya health tourism, namun kontribusi Kepolisian Daerah dalam pengembangan health tourism masih kurang maksimal. Kata kunci: health tourism; pengamanan wisatawan; Kepolisian Daerah